BIMBINGAN KONSELING ISLAM DALAM MEMBANGUN RELIGIUSITAS REMAJA DI SEKOLAH - Hapni, Elida; Akbar, Faisal; Ardimen, Ardimen (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
Today's teenagers tend to think positively about religious developments, so many of them do not yet consider themselves to be servants of God. Adolescence is a transition period between childhood and adulthood. Biological and psychological growth and development. So, with Islamic counseling guidance you can build the religiosity of teenagers at school. This research aims to determine the condition of adolescent religiosity at school and analyze the implementation of Islamic counseling guidance in building adolescent religiosity. This study used descriptive qualitative method. Descriptive qualitative research is a research procedure that produces descriptive data in the form of someone's words or utterances that need to be observed. The qualitative descriptive research referred to in this research is using an Islamic counseling guidance approach by describing the conditions and implementation of Islamic counseling guidance in building adolescent religiosity in schools. The research results show that the condition of adolescent religiosity at school has several aspects that need to be implemented, namely the need for parental attention, the need for religious practice, knowledge about religion, the consequences that will occur in adolescents. Then the teenage religiosity crisis is caused by family, environmental, social and social media factors